Advances in immunotherapy and targeted therapy for advanced clear-cell renal cell carcinoma: current strategies and future directions - Wang, Bo; Xiang, Yuchu; Liu, Xudong; Pan, Xiaoting; Peng, Lang; Ma, Jiajia (Frontiers in Immunology, 2025)
Renal cell carcinoma (RCC), particularly the clear-cell subtype (ccRCC), accounts for 75-85% of kidney cancers and exhibits distinct genetic and biological heterogeneity. While surgical resection remains the mainstay of treatment for localized ccRCC, the persistence of recurrence rates underscores the significant unmet need for effective adjuvant therapies. Recent advancements in immunotherapy and targeted therapies have revolutionized the management of RCC. Immune checkpoint inhibitors have significantly enhanced antitumor immune responses, whereas tyrosine kinase inhibitors (TKIs) and mammalian target of rapamycin (mTOR) inhibitors effectively disrupt angiogenesis and proliferation signaling pathways, respectively. However, non-clear cell RCC subtypes remain understudied due to their rarity and exclusion from major clinical trials. Consequently, this review primarily focuses on ccRCC, aiming to provide a comprehensive and up-to-date overview of the latest advancements in immunotherapy and targeted therapies. By synthesizing current evidence, this review seeks to elucidate the mechanisms of action, clinical efficacy, and limitations of these treatments, while also identifying gaps in knowledge and future research directions. Ultimately, the goal is to offer valuable insights for clinicians and researchers, facilitating the development of optimized, personalized treatment approaches to improve outcomes for ccRCC patients.